(untitled) (Proceedings of the International Conference on Future of Education, 2025)
The research course, oral thesis defense abilities determined research success. Text and defense go together. Panel examiners reviewed 34 English, Mathematics, and Science student papers for Teacher Education’s secondary education thesis proposal defense. Advisors, researchers, and three-panel examiners—the chairman, data analyst, field expert, and technical expert—rated the work. ANOVA parametric test was used since the normality scale p-value is 0.968 and the variances in all five areas—organization, content, speaking skills, question response, and confidence and personality—are more than 0.05. Comparison of oral proficiency to specialization course. Student specialization did not affect oral proficiency (p=0.075, mean=66.90%), however three of five were relevant. Content, answers, confidence, and personality varied by expertise. Scheffe’s assessment indicated that third-year Math and Science students performed equally in oral proficiency but differently from English majors. It’s amazing that English huge research groups fared worse than the two. The program needs improve since English majors may struggle in the three areas. All three majors had the same organization (p=0.060, mean=67.06%) and speaking ability (p=0.096, mean=65.29) since the other three categories were great but not significant. The study may help research facilitators, advisers, the department, and the research office boost student research by focusing on thesis defense oral abilities.